2023
DOI: 10.3390/cells12212538
|View full text |Cite
|
Sign up to set email alerts
|

Postbiotic Fractions of Probiotics Lactobacillus plantarum 299v and Lactobacillus rhamnosus GG Show Immune-Modulating Effects

Agnieszka Magryś,
Mateusz Pawlik

Abstract: Probiotic bacteria belonging to Lactobacillus spp. are important producers of bioactive molecules, known as postbiotics, that play essential roles in the immunological support of the intestinal mucosa. In this study, the system of co-culture of intestinal epithelial cells with macrophage cells in vitro was used to study the potential effect of postbiotic fractions of L. rhamonosus and L. plantarum on the modulation of the immune response induced by pro-inflammatory stimuli. This study’s results revealed that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Among the various LAB species, L. plantarum 299v and L. rhamnosus GG are the most commonly investigated strains and are also widely used in the pharmaceutical and food industries. Analysis of the postbiotic composition of these strains revealed the presence of several bioactive compounds with antineoplastic potential, which can interact with the host's immune system, modulate the tumor microenvironment, and exert a direct effect on cellular processes [31]. The products of bacterial metabolism with promising anticancer potential are short-chain fatty acids (SCFAs)-butyric, acetic, and propionic acids [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…Among the various LAB species, L. plantarum 299v and L. rhamnosus GG are the most commonly investigated strains and are also widely used in the pharmaceutical and food industries. Analysis of the postbiotic composition of these strains revealed the presence of several bioactive compounds with antineoplastic potential, which can interact with the host's immune system, modulate the tumor microenvironment, and exert a direct effect on cellular processes [31]. The products of bacterial metabolism with promising anticancer potential are short-chain fatty acids (SCFAs)-butyric, acetic, and propionic acids [29,32].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the use of products or supplements rich in live bacterial cultures, such as Bifidobacterium bifidum, Bifidobacterium lactis, Lactobacillus acidophilus, Lactobacillus brevis, Lactobacillus casei, Lactobacillus salivarius, or Lactobacillus lactis, has a positive effect in terms of improving overall well-being and the severity of depressive symptoms after about 3-4 weeks of their use, depending on the initial severity of the symptoms related to patients' mental functioning [131].…”
Section: Clinical Human Studies On Psychobioticsmentioning
confidence: 99%
“…Lactobacillus plantarum 299v and Lactobacillus rhamnosus GG suppress inflammation and protect against intestinal barrier damage through regulatory effects on LPS-mediated cytotoxic activity in intestinal epithelial cells [131].…”
Section: Lactobacillusmentioning
confidence: 99%
“…Their beneficial functions include, but are not limited to, antimicrobial and antioxidant properties, as well as modulation of intestinal barrier function and immune response. Much of the current postbiotic research is focused on Lactobacillus and Bifidobacterium , similar to probiotic organisms ( Magryś and Pawlik, 2023 ; Motei et al, 2023 ). Overall, postbiotics offer advantages that probiotics cannot match, including a well-defined chemical structure, safe dosage parameters, and a longer shelf life of up to 5 years as a nutritional additive.…”
Section: The Conception and Classification Of Postbioticsmentioning
confidence: 99%